2012
DOI: 10.3897/zookeys.207.3040
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic studies on genus Tetramorium Mayr (Hymenoptera, Formicidae) with report of two new species and three new records including a tramp species from India with a revised key

Abstract: Two new species of Tetramorium Mayr, namely Tetramorium shivalikense sp. n. and Tetramorium triangulatum sp. n. are described. Tetramorium triangulatum sp. n. belongs to the inglebyi-species group and is described based on worker, queen and male caste, while Tetramorium shivalikense sp. n. belongs to the ciliatum-species group and is described based on worker caste only. Three species viz., Tetramorium caldarium (Roger), Tetramorium tonganum Mayr and Tetramorium urbanii Bolton represent first records from Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
(8 reference statements)
0
17
0
Order By: Relevance
“…The updated list of Indian Tetramorium species given below is based on Bharti (2011) , Bharti & Kumar (2012) , and Bharti et al (2016) with some corrections and additions resulting from this study ( Tables 2 and 3 ). Currently, we recognize 42 species for the country ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The updated list of Indian Tetramorium species given below is based on Bharti (2011) , Bharti & Kumar (2012) , and Bharti et al (2016) with some corrections and additions resulting from this study ( Tables 2 and 3 ). Currently, we recognize 42 species for the country ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…230 valid and potentially 150 undescribed species are known ( Bolton, 1976 ; Hita Garcia, Fischer & Peters, 2010 ; Hita Garcia & Fisher, 2014a ). The Indomalayan region also harbors a rich Tetramorium fauna with approximately 120 species ( Janicki et al, 2016 ; Guénard et al, 2017 ), of which 42 have been reported from India ( Bharti et al, 2016 ; Bharti & Kumar, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These works provided an excellent foundation for the many later revisions or treatments of species groups/complexes or regions/subregions (e.g. Csösz et al 2007; Csösz and Schulz 2010; Hita Garcia et al 2010; Hita Garcia and Fisher 2011, 2012a, 2012b, 2013, 2014a, 2014b; Bharti and Kumar 2012; Sharaf et al 2012; Vásquez Bolaños et al 2011). The Malagasy Tetramorium fauna was first monographed by Bolton (1979), who treated eight species groups with 36 species (29 of these endemic to Madagascar).…”
Section: Introductionmentioning
confidence: 99%